2023
DOI: 10.1186/s13018-023-03592-0
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism after arthroscopic shoulder surgery: a systematic review

Abstract: Purpose To summarize the incidence, risk factors, diagnosis methods, prophylaxis methods, and treatment of venous thromboembolism (VTE) following arthroscopic shoulder surgery. Methods Literature on VTE after arthroscopic shoulder surgeries was summarized, and all primary full-text articles reporting at least 1 case of deep vein thrombosis (DVT) or pulmonary embolism (PE) after arthroscopic shoulder surgeries were included. Articles were critically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(268 reference statements)
0
1
0
Order By: Relevance
“…For example, in a significant group of cirrhotic patients who were admitted to the hospital, diabetes was identified as a separate indicator of portal vein thrombosis 32 . Also, another recent study 33 reported that diabetes is a possible risk factor for VTE after arthroscopic shoulder surgery. However, a study using bidirectional two‐sample Mendelian randomization 34 did not find any positive impacts of VTE on both Type 1 and Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a significant group of cirrhotic patients who were admitted to the hospital, diabetes was identified as a separate indicator of portal vein thrombosis 32 . Also, another recent study 33 reported that diabetes is a possible risk factor for VTE after arthroscopic shoulder surgery. However, a study using bidirectional two‐sample Mendelian randomization 34 did not find any positive impacts of VTE on both Type 1 and Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%